A cognitive-based ISAR system for spectral compatibility applications - Rosamilia, Massimo; Aubry, Augusto; Balleri, Alessio; De Maio, Antonio; Martorella, Marco (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper proposes and analyzes the concept of a cognitive inverse synthetic aperture radar (ISAR) ensuring spectral compatibility in crowded electromagnetic environments. In such a context, cognitive radar system alternates between a perception stage, recognizing possible emitters in its frequency range, and an action stage, synthesizing and transmitting a tailored radar waveform to achieve the desired task while guaranteeing the spectral coexistence with overlaid emitters. The perception stage is carried out by an electronic support measurement system (ESM) that senses the environment and extracts relevant spectral parameters. The action stage employs a tailored signal design process, synthesizing a radar waveform with bespoke spectral notches, enabling ISAR imaging over a wide spectral bandwidth without interfering with the other radio frequency (RF) systems. A key enabling technology for the proposed application is the compressed sensing (CS) framework, allowing accurate ISAR imaging even with missing data in the frequency domain (induced by spectral notches) and in the slow-time dimension (enabling the system to perform additional RF activities). The capabilities of the proposed system are assessed exploiting a dataset of drone measurements in the frequency band [13, 15] GHz. The results highlight the effectiveness of the proposed system to enable the spectral compatibility while delivering high-quality ISAR images.
Keywords: 40 Engineering; 46 Information and Computing Sciences; 4006 Communications Engineering; 4605 Data Management and Data Science; 4013 Geomatic Engineering